Supportive teachers, active students: Is teacher support a promising key to engaging students with and without migration backgrounds? - Simon Munk; Doris Holzberger; Ricardo Böheim; Tina Seidel (Frontiers in Education)
Students with and without migration backgrounds differ in terms of their achievement. One approach to reducing the gap between the two groups may be through equal participation in classroom discourse. Here, supportive teaching behavior can be particularly important for promoting student participation. Especially teacher support after a student has made a mistake, the so-called error culture in the classroom, could pave the way for students to become active participants. In this study, we analyzed whether error culture as a facet of teacher support could be a promising key to engaging students with and without migration backgrounds. To investigate the generalizability of the process across different subjects, we examined video data from 20 eighth-grade classrooms of academic-track secondary schools in both German Language Arts and Mathematics (N = 387 students). The results from nested hierarchical linear models indicate that error culture is related to student participation in German Language Arts but not in Mathematics. Interestingly, students with and without migration backgrounds did not differ in terms of their participation in classroom discourse. Furthermore, teachers’ positive error culture supported students’ participation irrespective of their migration background. Therefore, we encourage teachers to continue to pay attention to their error culture as this seems relevant for all students in the classroom.